Pengaruh Persepsi Sampling Statistik Resiko Audit ,Time Pressure dan Pengalaman terhadap Penggunaan Metode Sampling Audit - Ade damayanty Vina giovani (Pascasarjana STIE Amkop Makassar, 2020)
AbstractThe purpose of this study is to analyze the type of sampling method that is often used by auditors and to analyze the factors that influence the use of sampling methods by independent auditors. The technique of data collection is done by distributing questionnaires to the Auditor who works at the Public Accounting Firm registered in Makassar. While the data analysis techniques used were validity and reliability test analysis, multiple linear regression analysis, and horsmer-glue test. The results of the study found that the perception of sampling with the use of the audit sampling method had a positive and significant effect. The influence between the perception of audit risk and the use of the audit sampling method has a positive and significant effect. The influence of Time pressure is significant with the use of the audit sampling method, and the influence of experience with the use of audit sampling methods has a significant and positive effect. Keywords: statistical sampling, audit risk, time pressure, auditor experience.